Improve Efficiency of An Automated Photovoltaic Solar Tracker with Cooling System for Renewable Energy Application - Latiff, Mohamad Rizalludin; Abu Hassan, Omar; Ahmad, Muhammad Shukri; Norjali, Rasida; Zainal, Mohd Shamian (Progress in Engineering Application and Technology, 2020)
This project develop high efficiency of the solar tracker by  adding cooling system because solar panel has temperature coefficient that output power will decrease by a half of a percent for every degree the temperature rises and cooling system will reduce the temperature of solar panel. The main objective of  this project to utilize the maximum solar energy and generated high efficiency of solar system by using solar tracker with cooling system. This project use LDR sensor to determine the orientation of the sun rays and the input readings of the  LDR sensor will read and analyzed through C++ programming. Servo motor has been used to control the movement and rotation of the solar panel when servo receive PWM signals from the micro controller programmer and servo moved the solar panel and tracked the sun light by using LDR sensor. The data has been collected base on the Voltage (V), Current (mA) and Power (mW) that solar tracker produce with cooling system and without cooling system. The differences data collected has been analyzed that solar tracker can generated high efficiency with cooling system or without cooling system. This project presented a means of to utilize the maximum solar energy by using solar tracker. Specifically it demonstrated a solar tracker system solution for maximizing solar energy by using cooling system. This project system can be improved in the future by adding IOT system at solar tracker system or cooling system. The system can be remotely controlled the movement of solar tracker or control the operation of cooling system.